Maturity Assessment Methodology for HISMM - Hospital Information System Maturity Model. - Carvalho, João Vidal; Rocha, Álvaro; Abreu, António (Journal of Medical Systems, 2019)
Maturity models have been adopted in organizations from different sectors of activity, as guides and references for information system (IS) management. In the healthcare field, maturity models have also been used to deal with the enormous complexity and demands of hospital information systems (HIS). This article presents a research project that aimed to develop a new comprehensive model of maturity for a health area. HISMM (hospital information system maturity model) was developed to address the complexity of HIS and intends to offer a useful tool to meet the demands of its management. The HISMM has the peculiarity of combining a set of key maturity influence factors and their respective characteristics, enabling not only the assessment of the global maturity of an HIS but also of the individual maturities of its various dimensions. In this article, we present a methodology for the application and implementation of this model in HIS, thus contributing to its widespread practical application and acceptance.